Effect of Intradialytic Exercise on Haemodialysis Adequacy - Endrat Kartiko Utomo; Erna Rochmawati (University of Muhammadiyah Malang, 2019)
People with kidney failure should have hemodialysis therapy to survive. The effectiveness of hemodialysis therapy can be measured by calculating the value of dialysis adequacy: Kt/V and URR values. Intradialytic exercise is an exercise that can improve of dialysis adequacy. The purpose of this review is to report the results of related research on the effect of intradialytic exercise on dialysis adequacy. Relevant articles were search in PubMed, Science Direct and Google Scholar using this keywords intradialytic exercise and dialysis adequacy. Results: 12 articles ware included in the review and found various intradialytic exercises, intradialytic training time and length of intradialytic training. Exercises that can improve the adequacy of dialysis are static bike exercises, airogym and aerobics. While exercise resistance decreases the value of dialysis adequacy. We also found that the initial adequacy varied. Discussion: mild exercise can increase dialysis adequacy, in the first two hours of dialysis and minimum exercise was conducted two month. Currently no literature that recommend type and length of intradialytic exercise. Conclusion: intradialytic exercise can increase the value of dialysis adequacy, although it has increased, the mean value of adequacy before exercise is above standard. To confirm these findings, further research is needed to conducted exercise ware the value of adequacy under standard values.